Accuracy of three‐dimensionally printed animal‐specific drill guides for implant placement in canine thoracic vertebrae: A cadaveric study. Issue 2 (29th December 2020) - Mariani, Christopher L.; Zlotnick, Joshua A.; Harrysson, Ola; Marcellin‐Little, Denis J.; Malinak, Kristen; Gavitt, Ashley; Guevar, Julien
Abstract: Objective: To assess the accuracy of three‐dimensionally (3‐D) printed drill guides in constraining the trajectory of drill tracts for implants in canine thoracic vertebrae. Study design: Experimental ex vivo study. Sample population: Five canine thoracic vertebral column specimens. Methods: Guides to constrain drill trajectories were designed on the basis of computed tomographic (CT) imaging of six thoracic vertebrae (T8‐T13) and were 3‐D printed. The guides were used to create drill tracts in these vertebrae by both an experienced and a novice surgeon, and CT imaging was repeated. The entry point and angulation of actual and planned drill tracts were compared for both surgeons. Unintended cortical violations were also assessed by using a modified Zdichavsky classification. Results: Fifty‐eight drill tracts were created in 30 vertebrae. Mean entry point deviation was 1.4 mm (range, 0.4‐3.4), and mean angular deviation was 5.1° (range, 1.5°‐10.8°). There were no differences between surgeons in entry point deviation ( P = .07) or angular deviation ( P = .22). There were no unintended cortical bone violations, and all drill tracts were classified as modified Zdichavsky grade I. Conclusion: The 3‐D printed guides used in the current study yielded drill tracts with small linear and angular errors from intended paths and 100% accuracy for placement within vertebral pedicles and bodies. This technique was conveniently used by both an experienced and a novice surgeon. Clinical significance: This technique might be immediately applicable to clinical cases requiring thoracic vertebral stabilization and may allow safe and accurate implant placement for surgeons with varying experience levels.